And next year s winners? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
And next year s winners?Nominations close on 10 April 2001 for the next Right Livelihood Awards. They are granted to people whose achievements in, or service to, development initiatives and in popular science deserve replication. The award is US$...